(untitled) (Journal of the Bangladesh Agricultural University, 2025)
The study evaluated the economic viability of rooftop gardening in Dhaka, Bangladesh, focusing on its potential for income generation and associated constraints. A total of 60 gardeners were selected as samples from Kalabagan, Mohammadpur, Mirpur, Banani, Cantonment and Uttara areas. The data was analyzed using a mixed-method approach that included both descriptive and statistical techniques. The study found that rooftop vegetable gardening is economically viable, with a benefit-cost ratio of 1.32, indicating that every unit of money invested, generated a positive return. Moreover, the gardener’s decision to cultivate a particular crop was influenced by the profitability of that crop in different situations. The study also identified that most of the gardeners earned direct or indirect income by cultivating vegetables in their rooftop gardens though the income is not much compared to their total income. Multiple regression analysis revealed that the age of the gardeners, cost of seed/seedling/plant, cost of pesticide and insecticide, and cost of water were the most significant factors affecting the gross return from rooftop gardening. The SWOT analysis identifies strengths, such as food safety and environmental improvement, and challenges, such as low soil quality and limited availability of gardening equipment. According to this study, targeted training programs and market access for gardeners may increase rooftop gardening’s popularity and profitability in urban areas. J Bangladesh Agril Univ 23(2): 201-210, 2025